The Influence of Reliability and Digital Literacy on Intention to Use Application: The Mediating Role of Ease of Use at INAmikro, Jakarta: Pengaruh Reliabilitas Dan Literasi Digital Terhadap Niat Menggunakan Aplikasi, Dengan Kemudahan Penggunaan Sebagai Intervening Variabel, Di Inamikro, Jakarta - Mannjot Singh; Eddy (Jurnal Kolaboratif Sains, 2025)
INAmikro, Jakarta experienced a decline in users’ intention to use application that can be seen from the microApps activation this was suspected due to reliability, digital literacy and ease of use. The aim of this research is to investigate whether reliability and digital literacy on intention to use application with, ease of use as intervening variable, at INAmikro, Jakarta. Reliability, digital literacy and ease of use have an important role in shaping intention to use application. Reliability, digital literacy and ease of use are highly connected with intention to use application and microApps activation. In this research, the writer used quantitative research design and IBM SPSS statistics V. 26. The writer used descriptive and causal approach. The sampling technique used was convenience sampling. The sample size was 120 customers. This research also passed the validity, reliability, normality, multicollinearity, heteroscedasticity. The results of hypothesis test showed that reliability and digital literacy have partial influence on Ease of Use. Reliability, digital literacy and ease of use have partial an influence on intention to use application. Ease of use mediates the influence of reliability and digital literacy on intention to use application at INAmikro, Jakarta. Recommendations for INAmikro, Jakarta include can improve various microApps features that can be securely located, various rewards to customers, provides chat with staff so that if customer difficulties can be communicated can improve various security.